Zinc-blende compounds of transition elements with N, P, As, Sb, S, Se, and Te as half-metallic systems - Galanakis, I.; P. Mavropoulos (PHYSICAL REVIEW B, 2003)
We report systematic first-principles calculations for ordered zinc-blende compounds of the transition metal elements V, Cr, and Mn with the sp elements N, P, As, Sb, S, Se, and Te, motivated by a recent fabrication of zinc-blende CrAs, CrSb, and MnAs. They show a ferromagnetic half-metallic behavior for a wide range of lattice constants. We discuss the origin and trends of half-metallicity, present the calculated equilibrium lattice constants, and examine the half-metallic behavior of their transition element terminated (001) surfaces.